Denmark : Financial Sector Assessment Program-Technical Note-Next Steps for Cross-border AML/CFT Supervision. (IMF Staff Country Reports; Country Report, 2020)
The Danish authorities' efforts to strengthen cross-border anti-money laundering and combating the financing of terrorism (AML/CFT) supervision continue to gather momentum. Since the Fund's publication of a Selected Issues Paper on this subject in June 20192, the Danish authorities have made significant progress, including by conducting or participating in three multinational on-site inspections of banks; developing a new institutional risk assessment model; issuing an AML/CFT on-site inspection manual; and, via Act No. 1563 (2019), amending several pieces of legislation so as to bolster the monitoring and enforcement powers of the Danish Financial Supervisory Authority (DFSA), establish additional reporting requirements for the private sector, and stiffen the penalties for violations of AML/CFT obligations.